Study on the Steady-state Temperature Field of High Speed Spur Gear with Consideration of Elastohydrodynamic Lubrication - Fang Te; Liu Shaojun (Jixie chuandong)
Aiming at the real meshing state of high speed spur gear,the calculation mathematical model of line contact elastohydrodynamic lubrication is established,the model including Reynolds,elasticity and load balance equations etc. By using the numerical method,the friction factor of different meshing positions on the high speed spur gear under the elastohydrodynamic lubrication condition is solved. The thermal boundary conditions on different surfaces of gear teeth are obtained by using the friction and heat transfer theories. The single tooth network model of the high speed spur gear is established by using the combination thermal analysis method based on the Patran and Sinda software,and the steady-state temperature field distribution of the gear tooth is obtained. The steady-state temperature distribution of gear under the experimental condition is obtained by temperature measuring experiment on the gear experiment bench,and the simulation results are compared with the experiment result,and the feasibility of the simulation method is proved.